Fourier-type estimation of the power GARCH model with stable-Paretian innovations - Francq, Christian; Meintanis, Simos G. (Springer, 2016)
We consider estimation for general power GARCH models under stable-Paretian innovations. Exploiting the simple structure of the conditional characteristic function of the observations driven by these models we propose minimum distance estimation based on the empirical characteristic function of corresponding residuals. Consistency of the estimators is proved, and the asymptotic distribution of the estimator is studied. Efficiency issues are explored and finite-sample results are presented as well as applications of the proposed procedures to real data from the financial markets. A multivariate extension is also considered
Keywords: GARCH model; Minimum distance estimation; Heavy-tailed distribution; Empirical characteristic function